The urinary exosomes derived from premature infants attenuate cisplatin-induced acute kidney injury in mice via microRNA-30a-5p/mitogen-activated protein kinase 8 (MAPK8) - Ma, Mingming; Luo, Qiao; Fan, Lijing; Li, Weilong; Li, Qiang; Meng, Yu; Yun, Chen; Wu, Hongwei; Lu, Yongping; Cui, Shuang; Liu, Fanna; Hu, Bo; et al. (Bioengineered, 2022)
Acute kidney injury (AKI) is a susceptible factor for chronic kidney disease (CKD). There is still a lack of effective prevention methods in clinical practice. This study investigated the protective effect of the urinary exosomes from premature infants on cisplatin-induced acute kidney injury. Here we isolated exosomes from the fresh urine of premature infants. A C57BL/6 mice model of cisplatin-induced acute kidney injury was given 100 ug urinary exosomes 24 hours after model establishment. The kidneys were collected for pathological examination and the evaluation of renal tubular damage and apoptosis. In the in vitro experiment, human renal cortex/proximal tubular cells (HK-2) were induced by cisplatin to assess the effect of the urine exosomes from premature infants. Exosome microRNA (miRNA) sequencing technology was applied to investigate the miRNAs enriched in exosomes and the dual-luciferase gene reporter system to examine the targeting relationship of the miRNA with target genes. The results indicated that the urinary exosomes could decrease the serum creatinine level and the apoptosis of renal tubular cells, and reduce mice mortality. In addition, miR-30a-5p was the most abundant miRNA in the exosomes. It protected HK-2 cells from cisplatin-induced apoptosis by targeting and down-regulating the mitogen-activated protein kinase 8 (MAPK8). Together, our findings identified that the urinary exosomes derived from premature infants alleviated cisplatin-induced acute kidney injury and inhibited the apoptosis of HK-2 via miR-30a-5p, which could target MAPK8. These findings implied that urinary exosomes from premature infants riched in miR-30a-5p might become a potential treatment for AKI.
Gesehen am 04.05.2023